Ri’ayah dalam Pandangan Islam - Zainuddin, Zainuddin (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2021)
Islam consists of three main components: aqidah, worship and morals. These three components need to be harmonized in order to create harmony in religion. One of the things that need to be done in carrying out the religious component is to maintain it as well as possible. The nature of guarding and nurturing is called ri'ayah. The degrees of ri'ayah consist of ri'ayah al-a'mal (maintaining deeds), ri'ayah al-ahwal (maintaining circumstances) and ri'ayah al-awqat (maintaining time). Ri'ayah is done as proof of the sincerity of human self-servitude to Allah SWT and as a realization of the wisdom of its creation. The ultimate goal and the benefits derived from the maintenance is to get the pleasure of Allah SWT and His mercy in this world and the hereafter. Hadith of the Prophet Muhammad SAW also discusses this ri'ayah which is the reference for the people.ABSTRAKIslam terdiri dari tiga komponen utama, yakni akidah, ibadah dan akhlak. Ketiga komponen tersebut perlu diserasikan agar tercipta keharmonisan dalam beragama. Salah satu hal yang perlu dilakukan dalam  melaksanakan komponen agama tersebut adalah memeliharanya dengan sebaik baiknya. Sifat menjaga dan memelihara tersebut dinamakan ri’ayah. Derajat  ri’ayah terdiri dari ri’ayah al-a’mal (memelihara perbuatan), ri’ayah al-ahwal  (memelihara keadaan) dan ri’ayah al-awqat (memelihara waktu). Ri’ayah dilakukan sebagai bukti kesungguhan penghambaan diri manusia kepada Allah  swt. dan sebagai realisasi dari hikmah penciptaannya. Tujuan akhir dan manfaat  yang didapatkan dari pemeliharaan tersebut adalah mendapat rida Allah swt. dan  rahmat-Nya di dunia dan akhirat. Hadis Rasulullah saw. juga membahas tentang  ri’ayah ini yang menjadi referensi umat dalam melaksanakannya.